Performing Structure. Tempo in Glenn Gould’s “Goldberg Variations” - Michael Rector (Zeitschrift der Gesellschaft für Musiktheorie)
Particularly in the later stages of his career, Glenn Gould hoped to create large-scale structural coherence in multi-movement works through his choice of tempi. In a scripted conversation with music critic Tim Page, Gould described the “rhythmic reference point” in his 1981 recording of Bach’s “Goldberg Variations.” Gould’s process in the recording studio did not involve comparison of discrete sections of music; Gould listened to or played along with the end of the previous variation to set the tempo of the following variation. Empirical analysis of Gould’s 1981 recording shows how the processual logic of Gould’s execution contrasts with the architectural emphasis of the theoretical literature on proportional tempo. In this recording, proportional tempo relationships depend on large-scale slowing across entire movements. Despite being common in Gould’s recordings, these tempo shapes have not previously been described in the scholarly or popular literature; I argue that listeners do not perceive them as tempo per se, but as structure. This heard sense of structure is created in an area underdetermined by Bach’s notation and is based almost entirely on Gould’s decisions as a performer.